Integrating plant‐ and animal‐based perspectives for more effective restoration of biodiversity. Issue 1 (2nd February 2016) - McAlpine, Clive; Catterall, Carla P; Nally, Ralph Mac; Lindenmayer, David; Reid, J Leighton; Holl, Karen D; Bennett, Andrew F; Runting, Rebecca K; Wilson, Kerrie; Hobbs, Richard J; Seabrook, Leonie; Cunningham, Shaun; et al.
Abstract : Ecological restoration of modified and degraded landscapes is an important challenge for the 21st century, with potential for major gains in the recovery of biodiversity. However, there is a general lack of agreement between plant‐ and animal‐based approaches to restoration, both in theory and practice. Here, we review these approaches, identify limitations from failing to effectively integrate their different perspectives, and suggest ways to improve outcomes for biodiversity recovery in agricultural landscapes. We highlight the need to strengthen collaboration between plant and animal ecologists, to overcome disciplinary and cultural differences, and to achieve a more unified approach to restoration ecology. Explicit consideration of key ecosystem functions, the need to plan at multiple spatial and temporal scales, and the importance of plant–animal interactions can provide a bridge between plant‐ and animal‐based methods. A systematic approach to restoration planning is critical to achieving effective biodiversity outcomes while meeting long‐term social and economic needs.